2009
DOI: 10.1155/2009/832589
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Growth Factor-I in Protein-Energy Malnutrition during Rehabilitation in Two Nutritional Rehabilitation Centres in Burkina Faso

Abstract: Objective. To investigate the relationship between IGF-I and the nutritional status of West-African children hospitalised for nutritional rehabilitation. Patients and methods. A cohort study was performed in two centres for nutritional rehabilitation and education (CREN) in Burkina Faso. Children were followed and the anthropometric data as well as the capillary blood samples were taken on the 7th and on the 14th days after their admission. IGF-I levels were determined from dried blood spots on filter paper o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(39 reference statements)
2
4
0
Order By: Relevance
“…The findings are consistent with those of previous studies that observed the low levels of IGF1 in hospitalized children suffering from protein and energy malnutrition; the values were even lower in marasmus than in kwashiorkor children [4]. After the nutritional rehabilitation, IGF1 increased significantly in both children with kwashiorkor and marasmus but the values were still lower than in healthy children 14 days post-treatment [4]. Moreover, low levels of IGF1 in early life is known to be associated with late risk of NCDs (Non-Communicable Diseases), particularly diabetes [2].…”
supporting
confidence: 93%
See 1 more Smart Citation
“…The findings are consistent with those of previous studies that observed the low levels of IGF1 in hospitalized children suffering from protein and energy malnutrition; the values were even lower in marasmus than in kwashiorkor children [4]. After the nutritional rehabilitation, IGF1 increased significantly in both children with kwashiorkor and marasmus but the values were still lower than in healthy children 14 days post-treatment [4]. Moreover, low levels of IGF1 in early life is known to be associated with late risk of NCDs (Non-Communicable Diseases), particularly diabetes [2].…”
supporting
confidence: 93%
“…The stunted SAM survivors had even lower circulating IGF1 levels than other stunted children from similar low socio-economic communities [2]. The findings are consistent with those of previous studies that observed the low levels of IGF1 in hospitalized children suffering from protein and energy malnutrition; the values were even lower in marasmus than in kwashiorkor children [4]. After the nutritional rehabilitation, IGF1 increased significantly in both children with kwashiorkor and marasmus but the values were still lower than in healthy children 14 days post-treatment [4].…”
supporting
confidence: 90%
“…Protein intake, particularly including essential amino acids, will only result in induction of an anabolic state when energy intake is adequate [18]. Similar experience was demonstrated in malnourished children in Burkina Faso [19]. Fifty nine children aged less than 3 years were hospitalised for nutritional rehabilitation, of whom 55 had marasmus, 2 kwashiorkor and 2 marasmus and kwashiorkor.…”
Section: Nutritional Deficiency In Developing Countriesmentioning
confidence: 67%
“…Indeed, several studies have shown that malnourished mice are more susceptible to infection, thus mimicking one of the hallmarks of human malnutrition (20,21). Furthermore, nutritional rehabilitation after kwashiorkor results in increased IGF-1 levels, but the values are lower than in healthy children (32). In our mouse model, IGF-1 levels are fully restored by nutritional rehabilitation, suggesting that mice are more resilient than humans to early-life nutritional stress.…”
Section: Discussionmentioning
confidence: 99%